Functional status of rowers on kayaks in the process of preliminary selection - Bogush, V.; Bogatyirev, K.; Reznichenko, O.; Sokol, O.; Veselova, I.; Farionov, V. (Slobozhanskyi herald of science and sport, 2018)
Purpose: conduct a comprehensive study of the functional status of athletes specializing in rowing, for the subsequent determination of the prospects in this sport.